Analisis Kinerja Arus Lalu Lintas pada Ruas Jalan Slamet Riyadi – Tulukabessy Kota Ambon: Analysis of Traffic Flow Performance on the Slamet Riyadi - Tulukabessy road, Ambon City - Michael Bora; Anthoneta Maitimu; Penina T. Istia (Litera Academica Publishing, 2024)
The Jalan Slamet Riyadi section is one of the main connecting roads that connects vehicle flows from inside and outside the city of Ambon. This section of road is also one of the roads that has a high level of vehicle density because at this location there is a tourism center in the form of Peace Gong and Merdeka Square which makes this place very busy with people visiting. With the crowds that occur on this road section, vehicle congestion and traffic jams often occur. Objective: Research on the performance of the Slamet Riyadi - Tulukabessy road section, factors that influence the performance of the Slamet Riyadi - Tulukabessy road section. The method used is the Indonesian Road Capacity Manual method (MKJI 1997). The degree of saturation is determined based on the highest USIG and UR data recap results among the survey results for 3 days (Monday, Wednesday and Saturday) from 06:00 WIT – 18:00 WIT at each survey point. Based on the results of field calculations, it can be seen that the capacity (C) of the Slamet Riyadi road section Monday at 16.00-17.00 WIT is 1469 pcu/hour with a value of Degree of Saturation (Ds) = 1.91 and the capacity value at (C) Intersection D.I. Panjaitan Monday 17.00 – 18.00 WIT is 3328 pcu/hour with a value of Degree of Saturation (Ds) = 3.53. From the calculation results, it is known that the capacity on the Slamet Riyadi Section and D.I.Panjaitan Intersection is already past saturation, which will cause long queues during peak hour traffic conditions. The results of the analysis of the average speed on the Slamet Riyadi road section for 6 hours were found to be 30.85 Km/hour.